Suppressive Modulation of the Chick Forebrain Network for Imprinting by Thyroid Hormone: An in Vitro Study - Saheki, Yuriko; Aoki, Naoya; Homma, Koichi J.; Matsushima, Toshiya (Frontiers in Physiology, 2022)
The thyroid hormone 3,5,3’-triiodothyronine (T3) is considered to act acutely in the chick forebrain because focal infusion of T3 to the intermediate medial mesopallium (IMM) causes 4 to 6-day-old hatchlings to become imprintable approximately 30 min after the infusion. To understand the mechanism of this acute T3 action, we examined synaptic responses of IMM neurons in slice preparations in vitro. Extracellular field potential responses to local electrical stimulation were pharmacologically dissociated to synaptic components mediated by AMPA and NMDA receptors, as well as GABA-A and -B receptors. Bath-applied T3 (20~40 μM) enhanced the positive peak amplitude of the field potential, which represented the GABA-A component. Bicuculline induced spontaneous epileptic bursts by NMDA receptor activation, and subsequent application of T3 suppressed the bursting frequency. Pretreatment of slices with T3 failed to influence the synaptic potentiation caused by tetanic stimulation. Intracellular whole-cell recording using a patch electrode confirmed the T3 actions on the GABA-A and NMDA components. T3 enhanced the GABA-A response and suppressed the NMDA plateau potential without changes in the resting membrane potential or the threshold of action potentials. Contrary to our initial expectation, T3 suppressed the synaptic drives of IMM neurons, and did not influence activity-dependent synaptic potentiation. Imprinting-associated T3 influx may act as an acute suppressor of the IMM network.